The tooth wear influence assessment method of worm gears with involute worm on carrying capacity and durability - Чернець, М.В.; Чернець, Ю.М. (Problems of Tribology, 2014)
The modified tooth wear influence assessment method of worm gears with involute worm on contact strength, flexure radius and durability has been filed. As a result of numerical solution the regularities of tooth wear influence on the transmission parameters of the contact and tribocontact interaction have been established. They are presented graphically.